Contribuição ao conhecimento químico de espécies da família Asteraceae (Verbesina macrophylla (Cass.) S.F. Blake e Praxelis clematidea R.M. King & Robinson.) - Maia, Gabriela Lemos de Azevedo (2011)
The family Asteraceae is the largest angiosperm family and represents nearly 10% of the world's total flora. The family has been one of the most studied, in large part due to the promising chemical compounds produced by this group. Aiming at contributing to the chemotaxonomic study of the family Asteraceae , Praxelis clematidea e Verbesina macrophylla were submitted to a phytochemical study to isolate its chemical constituents, through usual chromatographic methods, and after identifying them by means of spectroscopic methods such as 1H and 13C NMR, with the add of two-dimensional techniques, besides comparison with literature data. Chemical study of the aerial parts of V. macrophylla resulted in the isolation of six compounds (p-coumaric acid, 6-E-p-cumaroil-4α-hydroxieudesmane, 6-Z-p-cumaroil- 4α-hydroxieudesmane, bornil-p-cis-cumarate, bornil-p-trans- coumarate and phydroxybenzoic acid). One flavone (5,7,3 ',4'-tetrahydroxyflavone) was isolated from ethyl acetate extract of the aerial parts of P. clematidea and six flavones were isolated from chloroform extract (4 ,5,7- trihydroxyflavone; 4 ,5-dihydroxy-7 methoxyflavone; 5-hydroxy-4´,7 dimethoxyflavone; 4 ,5,7- trimethoxyflavone; 5,4 - dihydroxy-6,7 dimethoxyflavone and 4 ,5,6,7- tetramethoxyflavone), all flavonoids are described by first time in the specie. The flavones of chloroform extract of P. clematidea were tested for their toxicity against Staphylococcus aureus SA-1199B, a strain possessing the NorA efflux pump. The flavones tested did not show any significant antibacterial activity against the Staphylococcus aureus strain used, but were able to modulate bacterial drug resistance. This property might be related to the degree of lipophilicity of the flavones conferred by the methoxyl groups, since 4 ,5,6,7 tetramethoxyflavone the most methoxylated compound, reduced the minimal inhibitory concentration of the drug (Norfloxacin)16-fold.